BALB/c mice vaccinated with Leishmania major ribosomal proteins extracts combined with CpG oligodeoxynucleotides become resistant to disease caused by a secondary parasite challenge - Ramírez, Laura (2010)
Universidad Autónoma de Madrid. Departamento de Biología Molecular. Centro de Biología Molecular Severo Ochoa. Madrid, Spain